PELATIHAN PEMASARAN PRODUK UMKM AKSESORIS MELALUI PLATFORM TIKTOK DI DESA TAMAN RAHAYU - Atika, Putri Amelia; Arrahim, Arrahim; Marginingsih, Ria (Universitas Islam 45 Bekasi, 2025)
Micro, small, and medium enterprises hold a significant role in supporting economic growth, yet many entrepreneurs continue to experience obstacles in adapting to digital marketing practices. One of these cases is Aksesoris Ibu Ratmi in Taman Rahayu Village, which still relies heavily on conventional marketing strategies, thereby limiting product visibility and sales potential. To address this issue, a community service program was implemented in the form of online marketing training through the use of the TikTok platform. The training was carried out with a practical approach that included step-by-step guidance in creating a TikTok business account, setting up a TikTok Shop, and producing as well as uploading creative video content tailored to the characteristics of accessories products. During the activity, participants received hands-on practice under direct mentoring to ensure the skills could be applied independently. The results showed that Ibu Ratmi successfully created her own business account and began utilizing TikTok as a marketing tool. However, some challenges remain, particularly in maintaining consistency in content creation and optimizing the use of all available features on the platform. Despite these limitations, the training has provided initial knowledge and practical skills that enable the entrepreneur to better understand digital marketing, expand market reach, and improve product competitiveness. In conclusion, this program has contributed positively to strengthening the capacity of local enterprises, although continuous assistance is recommended to maximize the potential of TikTok for long-term and sustainable business growth.